(untitled) (Indian Journal of Animal Production and Management, 2014)
A study was undertaken to study the breeding, feeding and housing management practices of Macherla Brown sheep in Guntur, Nalgonda, Prakasam and Krishna districts of Andhra Pradesh with sample size of 104 farmers. Study revealed that 62.5 % Macherla Brown sheep farmers in the breeding tract maintained one breeding ram for every 30-50 ewes. Majority (56%) of sheep farmers retained the breeding rams for 3-5 years, while 44% farmers retained breeding rams more than 5 years in their flocks for breeding purpose. 69% farmers followed extensive system of rearing without any supplementation and water was provided during grazing and housing time. 96% of the farmers provided housing to their animals in the form of night shelter. Majority of sheep farmers (61%) used thatched material as roofing material followed by asbestos sheets (31%) and tiles(3%).